The given limit has a finite result. Approximate the value of .
Bonus: Evaluate the limit.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
x → 0 lim x 2 x ! + α x − 1 We can rewrite the factorial function as its definition, the Γ ( x ) function x → 0 lim x 2 Γ ( x + 1 ) + α x − 1 Because the limit is in the form 0 0 , (note that Γ ( 1 ) = 1 ), we can us L'Hôpital's rule x → 0 lim 2 x Γ ′ ( x + 1 ) + α For the limit to give a finite result, it must not diverge. The limit will not diverge if the fraction is in the form 0 0 , (the form ∞ ∞ is unattainable in this case). Thus, Γ ′ ( x + 1 ) = − α Evaluating at x = 0 Γ ′ ( 1 ) = − α Evoking the definition of the Γ ( x ) function leads to Γ ( x ) = ∫ 0 ∞ e − t t x − 1 d t Taking the derivative on both sides with respect to x , (I am ignoring the Leibniz Rule of differentiation under the integral sign. For more info, look at notable resources below) Γ ′ ( x ) = ∫ 0 ∞ e − t t x − 1 ln ( t ) d t Evaluating at x = 1 Γ ′ ( 1 ) = ∫ 0 ∞ e − t ln ( t ) d t This is one of the integral definitions of the Euler-Mascheroni constant, thus Γ ′ ( 1 ) = − γ = − α α = γ = 0 . 5 7 7 2 1 In order to evaluate the limit, which is now x → 0 lim 2 x Γ ′ ( x + 1 ) + γ we will evoke L'Hôpital's rule once more x → 0 lim 2 Γ ′ ′ ( x + 1 ) 2 Γ ′ ′ ( 1 ) Using the Γ ′ ( x ) from earlier, which was Γ ′ ( x ) = ∫ 0 ∞ e − t t x − 1 ln ( t ) d t Taking the derivative once more on both sides with respect to x Γ ′ ′ ( x ) = ∫ 0 ∞ e − t t x − 1 ln 2 ( t ) d t Setting x = 1 Γ ′ ′ ( 1 ) = ∫ 0 ∞ e − t ln 2 ( t ) d t Γ ′ ′ ( 1 ) = γ 2 + 6 π 2
Thus our limit is then equal to 2 γ 2 + 6 π 2 ≈ 0 . 9 8 9
Notable Resources:
In depth analysis of the derivative of the Gamma Function
Gamma Function
Euler-Mascheroni constant